\(\left(x-4\right)^2-36=0\)
\(\Leftrightarrow\left(x-4\right)^2=36\)
\(\Leftrightarrow\left[{}\begin{matrix}x-4=6\\x-4=-6\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=10\\x=-2\end{matrix}\right.\)
Vậy ...
\(4x^2-12x=-9\)
\(\Rightarrow\left(2x\right)^2-2.2x.3+3^2=0\)
\(\Rightarrow\left(2x-3\right)^2=0\)
\(\Rightarrow2x-3=0\)
\(\Rightarrow2x=3\)
\(\Rightarrow x=\dfrac{3}{2}\)
Vậy ...
\(\left(x+8\right)^2=121\)
\(\Rightarrow\left[{}\begin{matrix}x+8=11\\x+8=-11\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=3\\x=-19\end{matrix}\right.\)
Vậy ...